Relationship of Patient Perceptions About Giving Informed Consent to Preoperative Patient Anxiety - Diana Lusiawati; Hesti Prawita Widiastuti; Diah Setiani (Asian Journal of Healthcare Analytics, 2023)
One of the follow-up actions from handling emergency cases in the hospital. Reducing the level of preoperative anxiety, patients need to be given information about the disease and the actions to be performed, providing information can be done before carrying out the surgical process. Researchers have also conducted interviews with 12 patients who will undergo surgery at RSUD dr. Abdul Rivai Kab. Berau in December 2021, it was found that the results of giving informed consent had been submitted by doctors, maybe even with the help of nurses to clarify the giving of informed consent. This study aims to determine the relationship between the perception of giving informed consent and the anxiety of preoperative patients at RSUD dr. Abdul Rivai Berau District. Shows that the results of the hypothesis test obtained a p value: 0.009, meaning that there is a relationship between patient perceptions about giving informed consent and preoperative patient anxiety.